(untitled) (Research, Society and Development, 2021)
Sleep participates in numerous physiological functions and is responsible for maintaining physical and psychological health. However, what is observed in medical students during the internship period is a very extensive workload that includes classes and internships, making the choice between sleep quality and good academic performance a necessity. This study aimed to characterize the sleep quality of medical internship students and assess the impact of sleep on the routine of medical students in the fifth and sixth year of the Medicine course. Data for the performance of the work were collected through an online form applied to boarding students in March 2021. The analysis was performed through the interpretation of data collection arranged in a spreadsheet in the Microsoft Office Excel 2016 system and in the Past 4.05 software. Thirty-six students participated in the study, among which 69.4% were women and 30.6% were men. It was observed that the average amount of hours spent by students was 6.03 (SD±0.84), which is lower than recommended, and the quality of the study is higher when students have more hours of sleep, thus demonstrating the impact of sleep on good academic performance, making fewer hours of study necessary to effectively consolidate content.